Current Diagnosis and Treatment of Irritable Bowel Syndrome - Suprapto, Akmal Primadian; Idrus, Muhammad Firhat (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2025)
Irritable bowel syndrome (IBS) is a common functional gastrointestinal disorder characterized by a combination of symptoms, including abdominal pain, bloating, and altered bowel habits, often without any identifiable organic cause. The diagnosis of IBS typically involves a thorough clinical evaluation, including a detailed patient history and symptom assessment, often guided by the Rome IV criteria. Laboratory tests and imaging studies are generally employed to rule out other conditions. Current treatment strategies for IBS are multifaceted, aiming to alleviate symptoms and improve quality of life. They include dietary modifications, pharmacological treatment for symptoms management, and psychological interventions. Emerging therapies, such as microbiome modulation and novel pharmacologic agents, are under investigation and hold promise for future management of IBS. Overall, an individualized approach to treatment, considering both physiological and psychological factors, is essential for optimal patient outcomes.Keywords: Irritable bowel syndrome, diagnosis, treatment